Juridical Review of the Crime of Forest Destruction by Communities Based on the Law Number 18 of 2013 - Zulfan Hakim (Program Pascasarjana Universitas Muhammadiyah Palu, 2025)
This study aims to: (1) To find out the legal impact of forest destruction by the community according to Law Number 18 of 2013 concerning the Prevention and Eradication of Forest Destruction (2) To find out the government's legal steps against the perpetrators of forest destruction based on Law Number 18 of 2013 concerning the Prevention and Eradication of Forest Destruction. The method used in this writing is to use an empirical research approach. The results of this study are (1) The legal impact related to the crime of forest destruction by the community according to Law Number 18 of 2013 concerning the Prevention and Eradication of Forest Destruction is regulated in several articles where the perpetrators of forest destruction can be subject to imprisonment and fines and the proceeds of criminal acts committed by the perpetrators of forest destruction can be confiscated and confiscated by the state based on court decisions with permanent legal force (2) The government's legal steps against forest destruction perpetrators based on Law Number 18 of 2013 concerning the Prevention and Eradication of Forest Destruction include making preventive efforts in the form of patrols carried out by the forest police and collaborating with other law enforcement apparatus, in addition to that, it is also necessary to establish an Institution for the prevention and eradication of forest destruction. The Research Suggestions are (1) The government should involve the community, in this case the Forestry Police, in an effort to overcome forest destruction, considering that the obligation to protect forests is not only the government's obligation but also the obligation of all people. (2) It is better for the government, in this case the Ministry of Forestry, to immediately establish an Institute for the Prevention and Eradication of Forest Destruction so that the handling of forest destruction can be carried out in an integrated and directed manner by the newly formed institution.